Tetramethylpyrazine attenuates periorbital allodynia and neuroinflammation in a model of traumatic brain injury - Zhijing Wang; Qi Wang; Cuijie Wang; Xiuzhen Xu; Hongmei Yu (BMC, 2017)
Abstract Background Traumatic brain injury (TBI) is a public health issue. As the major complaint in 51% of TBI patients, chronic pain is an important aspect in TBI treatment. Tetramethylpyrazine (TMP) is an important compound in Ligustrazine, an analgesic drug in traditional Chinese medicine, but its potential in relieving pain symptom in TBI has not been tested. We established a TBI mouse model with controlled cortical impact (CCI), and measured periorbital hypersensitivity with von Frey monofilaments. We examined activated microglia and astrocytes and the levels of substance P (SP) and inducible isoform of nitric oxide synthase (iNOS) with immunohistochemistry, measured mRNA and protein levels of proinflammatory cytokines with qPCR and enzyme-linked immunosorbent assay, respectively. Western blot was employed to detect molecules in NF-κB signaling pathway. Results TMP significantly attenuated periorbital hypersensitivity in TBI mice. Within 3 days after CCI, TMP attenuated activation of microglia and astrocytes, levels of SP, iNOS, and CGRP in trigeminal pathway, and levels of proinflammatory cytokines (including IL-6, TNF-α, IL-12). In isolated microglia, TMP attenuated the effects of lipopolysaccharide on the phosphorylation of cytoplasmic IKKα/β and IKB-α, and levels of nucleic p65. Conclusion TMP reversed periorbital hypersensitivity by limiting neuroinflammation at the primary stage of TBI, and could be a promising drug for pain treatment in TBI.